Microwave switch based on mixed waveguide-coaxial tee for the cavity pulse shaper - Bondarenko, I.N.; Gorbenko, E.A.; Krasnoshok, V.I. (Radiotekhnika, 2017)
The possibilities of microwave tee switches for the resonator pulse former are estimated. It is shown that the values of the pulse output power can reach units of MW with conversion factors above 102. The features of using a switch based on a waveguide-coaxial tee are studied to control the modes of accumulation and emission of energy of a high-Q resonator storage. The operability of the structure considered for obtaining nanosecond and subnanosecond pulses is shown.